2017
DOI: 10.1002/adem.201600835
|View full text |Cite
|
Sign up to set email alerts
|

On the Breakdown of SiC during the Selective Laser Melting of Aluminum Matrix Composites

Abstract: Selective laser melting (SLM) is used to produce a SiC reinforced aluminum metal matrix composite (AMMC, Al-12Si plus 10 vol% SiC) with laser energy densities ( E p ) between 20 and 80 J mm À3 . Microstructural analysis shows that at lower energies, SiC is present in the Al-12Si matrix; however, at higher energies there is a distinct lack of SiC particles and the extensive formation of Al 4 C 3 needles and primary Si particles. XRD analysis confirms a decrease in the volume of SiC and an increase in the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 30 publications
(43 reference statements)
2
27
0
Order By: Relevance
“…This was accompanied by the loss of SiC. It is also found that the extent of SiC breakdown was closely related to the laser energy density with higher laser density resulting in more break-down 45 . Two possible theories were proposed for the breakdown: reaction theory and melt theory, although no one theory could completely explain the results.…”
Section: Selective Laser Melting Of Aluminium Matrix Compositesmentioning
confidence: 90%
“…This was accompanied by the loss of SiC. It is also found that the extent of SiC breakdown was closely related to the laser energy density with higher laser density resulting in more break-down 45 . Two possible theories were proposed for the breakdown: reaction theory and melt theory, although no one theory could completely explain the results.…”
Section: Selective Laser Melting Of Aluminium Matrix Compositesmentioning
confidence: 90%
“…For example, Dadbakhsh and Hao performed simple mechanical mixing to produce composite powders of several Al alloy matrix powders and reinforcements that were successfully used for PBF-L. [26] However, it is more suitable to mix the metal matrix powder with reinforcement particles of micron size than of nanometer range, as the latter show a stronger tendency to agglomerate. Ghosh et al reported a mixture of micro-SiC particles with Al-4.5Cu-3Mg alloy matrix powders for PBF-L. [55] Similarly, studies on micro-SiC particles mixed with Al-12Si alloy powder were reported by Astfalck et al [56] Dadbakhsh et al used a powder mixture of Al-xwt% Fe 2 O 3 (x ¼ 5, 10, and 15) for PBF-L, produced by mechanical mixing.…”
Section: Composite Powder Productionmentioning
confidence: 96%
“…Ceramic reinforcements impart high strength, hardness, and EM along with high-temperature stability to the Al alloy matrices. The most commonly used reinforcements in AMMCs for PBF-L in the last few years are micron-sized SiC particles, [55,56] nanosized SiC particles, [87] nanosized Al 2 O 3 particles, [64,65,88,89] in situ formed Al 4 SiC 4 nanoparticles, [90][91][92] Fe 2 O 3 nanoparticles, [26] and in situ formed Fe 2 O 3 nanoparticles, [93,94] TiC nanopowder, [64,95] in situ TiB 2 nanoparticles, [53,54,96] AlN nanoparticles, [97] nanosized TiN, [98,99] quasicrystalline particles, [100] and CNTs. [67] The preferred matrices are mostly AlSi10Mg, [67] Al-12Si alloys, [31,[101][102][103] 7075, [50] and 2024, [104,105] while pure Al [100] was used in a few cases.…”
Section: Reinforcements and Matricesmentioning
confidence: 99%
“…This will also induce different phase formation and transformation in these prefabricated HEA layers. [94][95][96] Last but not least, although most of the additive manufacturing of BMGs is carried out in protective gas atmosphere, for example, high purity argon, there still exists a certain amount of oxygen in the fabrication chamber which may severely detriment the glass forming ability of the original BMGs powders. Moreover, it is known that the formation of BMGs requires a homogenous chemical distribution of the constituent elements [4] during the entire process.…”
Section: Additive Manufacturing and Requirements For Producing Bulk Mmentioning
confidence: 99%
“…When this comes to blended elemental HEA powders and laser-based additive manufacturing technique, in addition to the abovementioned different melting temperature and evaporation pressure of the principal elements, the different laser reflectivity of the elemental powders will also need to be considered because different laser reflectivity can cause different temperature rise in different elemental powders. [94][95][96] Last but not least, although most of the additive manufacturing of BMGs is carried out in protective gas atmosphere, for example, high purity argon, there still exists a certain amount of oxygen in the fabrication chamber which may severely detriment the glass forming ability of the original BMGs powders. [84,97] It is noteworthy that the BMGs feedstock for metal additive manufacturing especially the BMG powders produced using gas-atomization also contains an oxide layer on the powder particle surface, [98,99] or possibly a moisture skin similar to Al alloys.…”
Section: Additive Manufacturing and Requirements For Producing Bulk Mmentioning
confidence: 99%